The youngest egg of avian affinities from the Cretaceous of Patagonia - Fernández, Mariela Soledad (2018)
We report the youngest fossil egg of avian affinities from the Cretaceous (Allen Formation, Campanian-Maastrichtian) of Patagonia, Argentina. The fossil consists in most of the internal cast of a single egg, preserving some eggshell fragments on one of its poles. Its axes are 4.5 cm and 3.06 cm. The eggshell surface is smooth, and its thickness average is 400 µm. The eggshell has two layers, with an ornithoid basic type and a ratite morphotype. The well-developed mammillary layer is 154 µm thick, with petal-shaped mammillae, the continuous layer is 251 µm thick. Shell microstructure is consistent with Laevisoolithidae, an ootaxon traditionally associated with enantiornithid birds. The shape of fibers of the testaceous membrane (TM) is preserved; these are flattened, with a thickness of 1.1 µm and a width of 4.8 µm each. The arrangement of the fibers of the TM is random, similar to that observed in extant reptiles. EDAX analysis reported that fibers are enriched in traces of Mg, Al, Si, P, F, and K, elements that are also present in both extant and fossil shell membrane. Cladistic analysis performed is consistent with the avian affinities established on the basis of macro, micro and ultrastructural characteristics.